Synthesis and Fluorescence Property of Mn-Doped ZnSe Nanowires. (27th June 2010) - Han, Dongmei; Song, Chunfeng; Li, Xiaoyu
Abstract : Water-soluble Mn-doped ZnSe luminescent nanowires were successfully prepared by hydrothermal method without any heavy metal ions and toxic reagents. The morphology, composition, and property of the products were investigated. The experimental results showed that the Mn-doped ZnSe nanowires were single well crystallized and had a zinc blende structure. The average length of the nanowires was about 2-3 μ m, and the diameter was 80 nm. With the increase ofMn 2 + -doped concentration, the absorbance peak showed large difference. The UV-vis absorbance spectrum showed that the Mn-doped ZnSe nanowires had a sharp absorption band appearing at 360 nm. The PL spectrum revealed that the nanowires had two distinct emission bands centered at 432 and 580 nm.